Smitten: From domestic bliss to domestic violence in the Cook Islands and the Timeline of Abuse. Issue 2 (1st November 2015) - Anderson, Erica
The Cook Islands is an archipelago of fifteen tiny islands scattered across an area of the Pacific that is equivalent in size to Western Europe but with only 13, 500 inhabitants. This article describes and discusses the first research on domestic violence to have been conducted throughout the whole of the Cook Islands. Qualitative interviews were conducted on every inhabited island in the country. The participants were Cook Islands women who had been, or who still were, victims of domestic violence. The research aimed to discover whether there was domestic violence throughout the Cook Islands and to hear from the victims about their experiences. The research also had an overarching goal of ensuring that the victims' voices were paramount, in order that they could be heard. In this article, the women tell their compelling stories and, despite the fact that the women come from several different generations and are on isolated islands, the results show that there are remarkable similarities in their stories. These similarities include the methods and types of abuse they experienced and their resultant psychosocial problems. Lastly, the results show that when the similarities in the women's stories are synthesized and compared to existing, worldwide research, this leads to the theory of the Timeline of Abuse, which is published here for the first time.